N‐(Anilinoethyl)amide Melatonergic Ligands with Improved Water Solubility and Metabolic Stability. (26th July 2021) - Ferlenghi, Francesca; Mari, Michele; Gobbi, Gabriella; Elisi, Gian Marco; Mor, Marco; Rivara, Silvia; Vacondio, Federica; Bartolucci, Silvia; Bedini, Annalida; Fanini, Fabiola; Spadoni, Gilberto
Abstract: The MT2 ‐selective melatonin receptor ligand UCM765 ( N ‐(2‐((3‐methoxyphenyl)(phenyl)amino)ethyl)acetamide), showed interesting sleep inducing, analgesic and anxiolytic properties in rodents, but suffers from low water solubility and modest metabolic stability. To overcome these limitations, different strategies were investigated, including modification of metabolically liable sites, introduction of hydrophilic substituents and design of more basic derivatives. Thermodynamic solubility, microsomal stability and lipophilicity of new compounds were experimentally evaluated, together with their MT1 and MT2 binding affinities. Introduction of a m ‐hydroxymethyl substituent on the phenyl ring of UCM765 and replacement of the replacement of the N, N ‐diphenyl‐amino scaffold with a N‐ methyl‐ N ‐phenyl‐amino one led to highly soluble compounds with good microsomal stability and receptor binding affinity. Docking studies into the receptor crystal structure provided a rationale for their binding affinity. Pharmacokinetic characterization in rats highlighted higher plasma concentrations for the N‐methyl‐N‐phenyl‐amino derivative, consistent with its improved microsomal stability and makes this compound worthy of consideration for further pharmacological investigation. Abstract : A taste for stability : Compound 19 is a potent melatonin receptor agonist obtained from the structural optimization of UCM765, an MT2 ‐selective partial agonist active in vivo, but characterized by poor physicochemical and pharmacokinetic properties. Insertion of a bromine atom on the phenyl‐methylamino scaffold led to a more soluble derivative endowed with higher microsomal stability.